Persepsi Manfaat, Persepsi Kemudahan dan Persepsi Risiko Terhadap Keputusan Minat Penggunaan Ulang E-Wallet OVO - Rahmatiyani, Rahmatiyani; Bertuah, Eka (Jurnal Etnik: Ekonomi-Teknik, 2023)
The revolution towards digitalization has changed most aspects of people's lives. Along with technological developments, new innovations are also needed that can make various activities more practical, efficient and comfortable, especially in the financial sector. New innovations are also needed, especially in the financial sector. The Covid-19 pandemic has limited all direct contact activities and has had an impact on changing people's habits towards the payment system from cash to non-cash. Technology Acceptance Model (TAM) is a research model conducted to analyze the factors that influence the use of information technology. This study aims to analyze the effect of perceived benefits, perceived convenience, perceived risk on interest in reusing Ovo e-wallet in this study using a quantitative research approach. The design of this study used survey measurements using a data collection tool using a questionnaire through a Likert scale. Based on the results of research that has been conducted online using Google Forms, questionnaires were distributed to respondents who have used the ovo e-wallet application at least 2 times or more than the last 6 months, then respondents are domiciled in DKI Jakarta and surrounding areas. Respondents who were collected in this study were 101 respondents, then the data was processed using the multiple linear regression method. The results of data analysis carried out with the help of SPSS software version 28.0.0.0 Based on the results of data analysis to measure the validity test in this study, the variables of perceived benefits, perceived convenience, perceived risk and interest in reusing OVO e-wallet were declared valid with significant values and reliability tests. by using Cronbach's Alpha coefficient that the four variables are declared reliable with a significance value. Then the classical assumption test is carried out which includes the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. Based on the results of the analysis, it is known that the perceived benefits variable, perceived convenience simultaneously and partially have a positive and significant effect on the interest in reusing the ovo e-wallet, while the risk perception variable has no effect on interest. in reusing ovo e-wallet. Determination (R2) based on the value can be seen from the analysis of the effect of perceived benefits, perceived comfort, perceived risk of interest in reusing ovo e-wallet with a value of 0.524. The dependent variable to determine the results of the statistical test showed that the hypothesis was accepted, namely perceived benefits, perceived convenience, interest in reuse, while the hypothesis was rejected, namely perceived risk because it had no significant effect. Then from the analysis results obtained that the perceived benefit variable is the dominant variable..